STUDI HUBUNGAN KUALITAS PERAIRAN DENGAN INDEKS EKOLOGI BIOTA AKUATIK DI KAWASAN ESTUARI PANTAI PERMATA PILANG PROBOLINGGO - Tri Ayu Rachma Dewi; Mauludiyah Mauludiyah; Misbakhul Munir (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
The sustainable use of estuary areas is needed to maintain the sustainability. The purpose of this research is to know the relationship of water quality with ecological index of aquatic biota in The Permata Pilang Beach Estuary Area, Probolinggo. The method used is survey with data analysis Principal Component Analysis. The results of showed that the temperature was 31.5-33.6°C, pH of 8.1-8.2, salinity of 1.6-32.1 ppt, DO of 11.1 – 11.8 mg/L, and water transparency of 0.5-1 meters. The grain size of the sediment is dominated by the fine sand. Found 20 species of macrozoobenthos which consisted of 10 species of gastropods and 10 species of bivalve. Fish community structure found 3 fish species (Chanos chanos, Mugil cephalus, Acentrogobius audax). The results of PCA analysis, it was found that the diversity of macrozoobenthos has a positive relationship with temperature and pH. The evenness of macrozoobenthos has a positive relationship with temperature, the dominance of macrozoobenthos has a positive relationship with salinity, pH, DO and water transparency. Fish diversity and evenness had a positive relationship with temperature and DO. Fish domination index has a positive relationship with salinity, pH and water transparency.